2003
DOI: 10.1007/978-3-540-45224-9_63
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Personality and Emotion Simulation

Abstract: Abstract. This paper describes a generic model for personality, mood and emotion simulation for conversational virtual humans. We present a generic model for describing and updating the parameters related to emotional behaviour. Also, this paper explores how existing theories for appraisal can be integrated into the framework. Finally we describe a prototype system that uses the described models in combination with a dialogue system and a talking head with synchronised speech and facial expressions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(31 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…Egges et al [9] have provided virtual characters with conversational emotional responsiveness. Elliott et al [10] demonstrated tutoring systems that reason about users' emotions.…”
Section: Relevant Workmentioning
confidence: 99%
“…Egges et al [9] have provided virtual characters with conversational emotional responsiveness. Elliott et al [10] demonstrated tutoring systems that reason about users' emotions.…”
Section: Relevant Workmentioning
confidence: 99%
“…However, it focuses on building specific and unique believable characters, where the goal is artistic abstraction of reality, not biologically plausible behavior. Egges describe a generic model [10] and generate emotional, communicative and multiple character animations [11]. Perlin [12] create the autonomous digital actor to act out scenes using procedural animation techniques.…”
Section: Related Workmentioning
confidence: 99%
“…One of the most popular personality models (the OCEAN model) describe personalities by five traits: openness, conscientiousness, extraversion, agreeableness and neuroticism [Egges et al 2003]. …”
Section: Personality Functionmentioning
confidence: 99%
“…There are several works that aim at describing how to model, implement and possible applications of virtual humans in terms of behavioral simulation (e.g. [de Sevin and Thalmann 2005;Kshirsagar and Thalmann 2002;Egges et al 2003]) which, in general, lies on psychological models that aim at mimicking real humans in a given context. One common feature that most of these works has described is to use personality traits and emotion models as a way of producing autonomous believable characters capable of showing individuality in such a way that they seem to be motivated by those characteristics just like any human.…”
Section: Virtual Humansmentioning
confidence: 99%